An intrinsic dual-emitting gold thiolate coordination polymer, [Au(+I)(p-SPhCO2H)]n, for ratiometric temperature sensing. Issue 38 (26th September 2017) - Veselska, Oleksandra; Okhrimenko, Larysa; Guillou, Nathalie; Podbevšek, Darjan; Ledoux, Gilles; Dujardin, Christophe; Monge, Miguel; Chevrier, Daniel M.; Yang, Rui; Zhang, Peng; Fateeva, Alexandra; Demessence, Aude
Abstract : Lamellar gold(i )-carboxythiophenolate exhibits intrinsic dual emission and a high sensitivity as a ratiometric thermometer. Abstract : The structure of a new lamellar gold thiolate coordination polymer is described. [Au(+I)( p -SPhCO2 H)] n exhibits unique bent S–Au–S angles due to the presence of both aurophilic and hydrogen interactions. More interestingly, this compound is the first coordination polymer displaying intrinsic dual emission in a large temperature range, from 80 to 320 K, with a maximum sensitivity of 3% K −1 at 260 K, and it possesses high potential as an optical temperature sensor.